2013 IEEE 54th Annual Symposium on Foundations of Computer Science 2013
DOI: 10.1109/focs.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Layered Separators for Queue Layouts, 3D Graph Drawing and Nonrepetitive Coloring

Abstract: Abstract-Graph separators are a ubiquitous tool in graph theory and computer science. However, in some applications, their usefulness is limited by the fact that the separator can be as large as Ω( √ n) in graphs with n vertices. This is the case for planar graphs, and more generally, for proper minor-closed families. We study a special type of graph separator, called a layered separator, which may have linear size in n, but has bounded size with respect to a different measure, called the breadth. We prove tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Together with the fact that planar graphs have layered 2-separators [13,19], these results imply an O(log n) bound for the queue-number of planar graphs, improving on a earlier result by Di Battista et al [10]. The polylog bound on the queue-number of planar graphs extends to all proper minor-closed families of graphs [15,16]. Our approach to prove Theorem 1 also gives a new proof of the following result (without using track layouts).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Together with the fact that planar graphs have layered 2-separators [13,19], these results imply an O(log n) bound for the queue-number of planar graphs, improving on a earlier result by Di Battista et al [10]. The polylog bound on the queue-number of planar graphs extends to all proper minor-closed families of graphs [15,16]. Our approach to prove Theorem 1 also gives a new proof of the following result (without using track layouts).…”
Section: Introductionsupporting
confidence: 68%
“…Layered separators are a key tool for proving our results. They have already led to progress on long-standing open problems related to 3D graph drawings [11,15] and nonrepetitive graph colourings [13]. A layering {V 0 , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A layering of a graph is a partition of the vertices into a sequence of disjoint subsets (called layers) such that each edge joins vertices in the same layer or consecutive layers. One way, but not the only way, to obtain a layering is the breadth first layering in which we partition the vertices by their distances from a fixed starting vertex [17,18]. We emphasis that a layering does not specify an ordering of the vertices within each layer, so there is no notion of edge crossings in a layering.…”
Section: Tree Decompositionsmentioning
confidence: 99%
“…The layered width of layered tree decomposition is the size of the largest intersection of a bag with a layer. The layered treewidth of a graph G is the minimum layered width of a tree-decomposition of G. Dujmović, Morin, and Wood [17,18] introduced layered treewidth and proved that every planar graph has layered treewidth at most 3, that every graph with Euler genus g has layered treewidth at most 2g + 3, and more generally that a minor-closed class has bounded layered treewidth if and only if it excludes some apex graph. Dujmović, Eppstein, and Wood [11,12] showed that layered treewidth is of interest well beyond minor-closed classes.…”
Section: Tree Decompositionsmentioning
confidence: 99%